A New Direct, Fast and Quantitative Enzyme-linked Ligandsorbent Assay for Measurement of Free Protein S Antigen - Giri, Tusar Kanti; Hillarp, Andreas; Härdig, Ylva; Zöller, Bengt; Dahlbäck, Björn (Thrombosis and Haemostasis, 1998)
A new method to determine the concentration of free protein S in plasma is described. It is an enzyme-linked ligandsorbent assay (ELSA) which utilises the protein S binding capacity of the natural ligand C4b-binding protein (C4BP) to capture the free protein S from plasma samples. The use of C4BP as ligand in the assay is possible due to the high affinity (Kd = 0.1 nM) of the interaction between protein S and C4BP and to a slow rate of complex dissociation. A monoclonal antibody (HPS 54) was conjugated with horseradish peroxidase and used as target antibody. This antibody recognises a Ca2+ dependent epitope in the first EGF-like domain of protein S and does not interfere with C4BP binding sites of protein S. Addition of calcium in the assay helped prevent dissociation of the C4BP-protein S-HPS 54 complex. Three different experiments demonstrated the assay to be specific for free protein S. First, near-identical dose response curves were obtained with protein S in plasma and with purified protein S. Second, addition of purified C4BP to normal plasma resulted in loss of free protein S. Third, protein S depleted plasma gave zero values and around 80% of purified protein S added to protein S depleted plasma, and approximately 70% of protein S added to protein S deficient plasma samples, was recovered with the assay. The assay is fast (involves only a single incubation step of 30 min), sensitive and the range of measurement is 3% to 200% of free protein S when plasma dilution 1 : 20 represents 100%. Intra- and inter-assay coefficients of variation at two levels were 2.3-4.3% and 5.1-7.4%, respectively. In a large protein S deficient family, the assay showed 100% sensitivity and specifity for the causative mutation. Moreover, free protein S levels in anticoagulated protein S deficient patients were completely separated from those obtained in non-anticoagulated controls. The new assay for free protein S is suitable for automation and it provides a useful means for routine clinical purposes to detect protein S deficiencies.